Disulfide bonds and disorder in granulin‐3: An unusual handshake between structural stability and plasticity. (22nd June 2017) - Ghag, Gaurav; Holler, Christopher J.; Taylor, Georgia; Kukar, Thomas L.; Uversky, Vladimir N.; Rangachari, Vijayaraghavan
Abstract: Granulins (GRNs) are a family of small (∼6 kDa) proteins generated by the proteolytic processing of their precursor, progranulin (PGRN), in many cell types. Both PGRN and GRNs are implicated in a plethora of biological functions, often in opposing roles to each other. Lately, GRNs have generated significant attention due to their implicated roles in neurodegenerative disorders. Despite their physiological and pathological significance, the structure‐function relationships of GRNs are poorly defined. GRNs contain 12 conserved cysteines forming six intramolecular disulfide bonds, making them rather exceptional, even among a few proteins with high disulfide bond density. Solution NMR investigations in the past have revealed a unique structure containing putative interdigitated disulfide bonds for several GRNs, but GRN‐3 was unsolvable due to its heterogeneity and disorder. In our previous report, we showed that abrogation of disulfide bonds in GRN‐3 renders the protein completely disordered (Ghag et al., Prot Eng Des Sel 2016). In this study, we report the cellular expression and biophysical analysis of fully oxidized, native GRN‐3. Our results indicate that both E. coli and human embryonic kidney (HEK) cells do not exclusively make GRN‐3 with homogenous disulfide bonds, likely due to the high cysteine density within the protein. Biophysical analysis suggests that GRN‐3 structure is dominated by irregular loops held together only by disulfide bonds, which induced remarkable thermal stability to the protein despite the lack of regular secondary structure. This unusual handshake between disulfide bonds and disorder within GRN‐3 could suggest a unique adaptation of intrinsically disordered proteins towards structural stability.